Distribution of CTX-M group I and group III β-lactamases produced by Escherichia coli and klebsiella pneumoniae in Lahore, Pakistan. (February 2017) - Abrar, Samyyia; Vajeeha, Ayesha; Ul-Ain, Noor; Riaz, Saba
Abstract: Extended-spectrum-lactamases (ESBLs) of the CTX-M type is worrisome issue in many countries of the world from past decade. But little is known about CTX-M beta -lactamase producing bacteria in Pakistan. Therefore, this study was carried out to investigate the distribution of CTX-M beta -lactamase producing E. coli and Klebsiella pneumoniae using phenotypic and molecular techniques. A total of 638 E. coli and 338 Klebsiella pneumoniae were isolated from patients attending two hospitals and one diagnostic Centre in Pakistan during 2013–2015. ESBL production was screened by double disc synergism, combination disc (cefotaxime and ceftazidime with clavulanic acid) and E-test. These strains were further characterized by PCR (CTX-M I, CTX-M III) and sequencing. After ribotyping of strains accession numbers were obtained. These isolates were highly resistant to cephalosporins, ceftazidime, cefotaxime, aztreonam, and cefuroxime but susceptible to carbapenems, sulfzone, amikacin and tazocin. Multiple antibiotic resistances index (MAR) revealed that 51% of E. coli strains fell in the range of 0.61–0.7 and 39% of Klebsiella pneumoniae strains fell in the range of 0.71–0.8. 64% Double disc synergism (DDS), 76.4% combination disc (CD), 74% E-test showed ESBL positivity in strains. In E. coli ESBL genes bla CTX-M-I and bla CTX-M-III were detected in 212 (72.1%) and 25 (8.5%) respectively. In Klebsiella pneumoniae ESBL genes bla CTX-M-I and bla CTX-M-III were detected in 89 (82.4%) and 10 (9.2%). Combination of both genes bla CTX-M-I and bla CTX-M-III were found in 16 (5.4%) of E. coli strains and 5 (4.6%) of Klebsiella pneumoniae strains. Sequencing revealed that CTXM-15 was predominately present in the CTX-M-I group. The prevalence of ESBL producing E. coli and Klebsiella pneumoniae isolates was high and the majority of them positive for bla CTX-M-I as compared to bla CTX-M-III. These findings highlight the need to further investigate the epidemiology of other CTX-M beta-lactamases in Pakistan.